2003
DOI: 10.1103/physrevlett.91.226101
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Analysis and Regeneration of Rough Surfaces

Abstract: We investigate Markov property of rough surfaces. Using stochastic analysis we characterize the complexity of the surface roughness by means of a Fokker-Planck or Langevin equation. The obtained Langevin equation enables us to regenerate surfaces with similar statistical properties compared with the observed morphology by atomic force microscopy.Studying the growth, formation and morphology of interfaces has been one of the recent interesting fields of study because of its high technical and rich theoretical a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(66 citation statements)
references
References 17 publications
1
65
0
Order By: Relevance
“…Successful attempts have been made to describe these systems as processes in scale rather than time or space itself. Examples are the description of roughness of surfaces [1,2], turbulence [3,4,5], earthquakes [6] and finance [7,8]. These successful attempts are characterised by the fact, that they can correctly provide the joint probability density function p(y 1 (τ 1 ), ..., y n (τ n )) of the increments y(τ ) of the process variable x at different scales τ , y(t, τ ) := x(t) − x(t − τ ).…”
Section: Introductionmentioning
confidence: 99%
“…Successful attempts have been made to describe these systems as processes in scale rather than time or space itself. Examples are the description of roughness of surfaces [1,2], turbulence [3,4,5], earthquakes [6] and finance [7,8]. These successful attempts are characterised by the fact, that they can correctly provide the joint probability density function p(y 1 (τ 1 ), ..., y n (τ n )) of the increments y(τ ) of the process variable x at different scales τ , y(t, τ ) := x(t) − x(t − τ ).…”
Section: Introductionmentioning
confidence: 99%
“…Illustration of the model: free diffusion within the channel and channel walls in y-and z-directions (reflective boundaries). Table 1 Applications of intrinsic transport coefficients Turbulence [3] Human tremor [7] Engineering [4] Surface sciences [8] Economics [5] Traffic [9] Time-delayed systems [6] Porous materials [2] Reaction-diffusion systems [10] that the definition of diffusion tensors by means of BD theory is not affected by the presence or absence of external or internal forces. More precisely, the evolution of the MSD components will of course depend for large times on the detailed forces acting on and between the fluid particles in a nanoporous material.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that in the saturate state the structure of topography has fractal feature with fractal dimension D f = 1.30. In addition, Langevin characterization of the etched surfaces enable us to regenerate the rough surfaces grown at the different etching time, with the same statistical properties in the considered scales 15 .…”
Section: Discussionmentioning
confidence: 99%
“…P (h, x) in terms of the length scale x. Recently some authors have been able to obtain a Fokker-Planck equation describing the evolution of the probability distribution function in terms of the length scale, by analyzing some stochastic phenomena, such as rough surfaces 15,16,17 , turbulent system 18 , financial data 19 , cosmic background radiation 20 and heart interbeats 21 etc. They noticed that the conditional probability density of field increment satisfies the Chapman-Kolmogorov equation.…”
Section: Introductionmentioning
confidence: 99%